Selected problems associated with the treatment and care for patients with colostomy – part 2 - Muzyczka, Katarzyna; Kachaniuk, Hanna; Szadowska-Szlachetka, Zdzisława; Charzyńska-Gula, Marianna; Kocka, Katarzyna; Bartoszek, Agnieszka; Celej-Szuster, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2013)
Generally, ostomy is a purposeful connection of the lumen of the intestine with abdominal integuments by surgery. The study presents practical solutions related to care for the colostomy patient, i.e. an ostomy on the large intestine. The following issues will be discussed: regulating the defecation cycle, risk connected with improper selection of ostomy equipment, instruction on colostomy irrigation with practical advice and irrigation equipment supply. The knowledge of these rules and mastering them in practice is to provide ostomy patients not only with highest-standard care and help but also to prepare them for dealing with problems independently, i.e. for self-care.